2011
DOI: 10.1371/journal.pone.0022732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Constitution on Mass of Individual Organs and Their Association with Metabolic Rate in Humans—A Detailed View on Allometric Scaling

Abstract: Resting energy expenditure (REE)-power relationships result from multiple underlying factors including weight and height. In addition, detailed body composition, including fat free mass (FFM) and its components, skeletal muscle mass and internal organs with high metabolic rates (i.e. brain, heart, liver, kidneys), are major determinants of REE. Since the mass of individual organs scales to height as well as to weight (and, thus, to constitution), the variance in these associations may also add to the variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 29 publications
4
54
1
1
Order By: Relevance
“…This is an often quoted use of allometry (e.g., 149,200,235,246,247,256,267,268,287,289) and is particularly prevalent in the human literature where scaling principles have been used to predict rates of metabolism (e.g., 172, 173, 284) and drug clearance (e.g., 396,397,398). Such analyses of intraspecific scaling for humans now routinely include data for metabolic rate and organ sizes of hundreds of individuals, and have been particularly useful for establishing the influence of body composition and stature on the scaling of metabolic rate with size (171,172,173,284), and for estimating in vivo metabolic rates of organ-tissue compartments (409,410). Scaling relationships can also be applied to the prediction of physiological characteristics of extinct species (114,270,348,359,361,368), and, because of the allometric relationship between body mass and other morphological variables, can be used to predict morphological characteristics that are (440) shown ± SEM and compared with predicted BMR for a 33 g murid rodent (shown ± SEE) for the OLS and PIC regressions presented in (A).…”
Section: Using Scaling Relationships Predicting Traits From Body Massmentioning
confidence: 99%
“…This is an often quoted use of allometry (e.g., 149,200,235,246,247,256,267,268,287,289) and is particularly prevalent in the human literature where scaling principles have been used to predict rates of metabolism (e.g., 172, 173, 284) and drug clearance (e.g., 396,397,398). Such analyses of intraspecific scaling for humans now routinely include data for metabolic rate and organ sizes of hundreds of individuals, and have been particularly useful for establishing the influence of body composition and stature on the scaling of metabolic rate with size (171,172,173,284), and for estimating in vivo metabolic rates of organ-tissue compartments (409,410). Scaling relationships can also be applied to the prediction of physiological characteristics of extinct species (114,270,348,359,361,368), and, because of the allometric relationship between body mass and other morphological variables, can be used to predict morphological characteristics that are (440) shown ± SEM and compared with predicted BMR for a 33 g murid rodent (shown ± SEE) for the OLS and PIC regressions presented in (A).…”
Section: Using Scaling Relationships Predicting Traits From Body Massmentioning
confidence: 99%
“…This research builds upon the quickly advancing development of imaging techniques, particularly computer tomography and magnetic resonance imaging (MRI), allowing for the quantification of the organ size in vivo and their contribution to variation in human BMR (e.g. Later et al 2008; Javed et al 2010; Müller et al 2002, 2011). For example, Elia (1992) estimated the mass-specific metabolic rates (in kcal/kg per day) of major human organs of young adults to be: 200 for liver, 240 for brain, 440 for heart and kidneys, 13 for skeletal muscle, 4.5 for adipose tissue and 12 for residual mass.…”
Section: Composition Of Bmr At Organ Levelmentioning
confidence: 99%
“…These estimates were recently validated with the use of imaging technologies, which also allowed for the fine-tuning of Elia’s estimates with respect to the effect of gender differences (Wang et al 2011a) and obesity (Wang et al 2011b). Likewise, a recent imaging-based comprehensive analysis of the scaling of human BMR and organ masses revealed that muscle, brain and liver explained up to 43 % of the inter-individual variance in human BMR (Müller et al 2011). …”
Section: Composition Of Bmr At Organ Levelmentioning
confidence: 99%
“…In fed subjects the estimated glycogen concentrations of the liver ( C liv ) (Nilsson, 1973; Rothman et al, 1991; Taylor et al, 1996; Petersen et al, 2004; Awad et al, 2010) approximate 500 mmol/kg dry weight and in muscle ( C sk ) 300 mmol/kg dry weight. Müller et al (Müller et al, 2011) published scaling relationships for total muscle mass by DXA and liver mass from MRI scanning in 262 adult humans. These were muscle mass (kg) =0.93× BW 0.76 and liver mass (g) =0.1× BW 0.62 .…”
Section: Methods and Resultsmentioning
confidence: 99%